Dermatology : Illustrated Study Guide and Comprehensive Board Review - Jain, Sima (Springer International Publishing : Imprint: Springer, 2017)
A fully-illustrated, note-packed volume of information, Dermatology: Illustrated Study Guide and Comprehensive Board Review fulfills a real need for a single study guide for the Dermatology Board Exam. Written by a previous Chief Resident of Dermatology at the University of Illinois at Chicago Medical Center, the text focuses on presenting comprehensive information in an easy-to-understand, easy-to-remember format. The second edition of this incredibly popular book includes updated coverage of new medications, new entities, and over 300 additional full-color clinical and histological images. Following the layout of the successful first edition, even more tips, short lists, and tables, including mnemonics and memory tricks to mentally organize information fill every inch of this book - a must-have for any dermatologist and dermatology resident.